2020
DOI: 10.1038/s41598-019-57388-6
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxin-3 is dispensable for basal neurotransmission and synaptic plasticity in postsynaptic hippocampal CA1 neurons

Abstract: Recent evidence suggests that SNARE fusion machinery play critical roles in postsynaptic neurotransmitter receptor trafficking, which is essential for synaptic plasticity. However, the key SNAREs involved remain highly controversial; syntaxin-3 and syntaxin-4 are leading candidates for the syntaxin isoform underlying postsynaptic plasticity. In a previous study, we showed that pyramidalneuron specific conditional knockout (cKO) of syntaxin-4 significantly reduces basal transmission, synaptic plasticity and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
(60 reference statements)
1
13
0
Order By: Relevance
“…Increasing evidence implicates a postsynaptic SNARE complex in AMPAR insertion during LTP ( 1520 ). We previously showed that shRNA-mediated knockdown of a critical component of this postsynaptic SNARE complex, Syntaxin-3 ( Stx3 ), in CA1-region neurons impaired LTP while sparing basal synaptic transmission ( 16 , 17, but see ( 21 ) for an opposing view). In the current set of experiments, we explored whether we could use Stx3 as a molecular handle to selectively probe the role of LTP in population coding and memory formation.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence implicates a postsynaptic SNARE complex in AMPAR insertion during LTP ( 1520 ). We previously showed that shRNA-mediated knockdown of a critical component of this postsynaptic SNARE complex, Syntaxin-3 ( Stx3 ), in CA1-region neurons impaired LTP while sparing basal synaptic transmission ( 16 , 17, but see ( 21 ) for an opposing view). In the current set of experiments, we explored whether we could use Stx3 as a molecular handle to selectively probe the role of LTP in population coding and memory formation.…”
Section: Main Textmentioning
confidence: 99%
“…An experience dependent representation likely already exists in the CA3-region. A computational model from the original publication (21) suggests that such remapping does not require CA1 specific circuitry. This upstream representation can likely be inherited even without plasticity (Fig S14).…”
Section: Supplementary Materials Formentioning
confidence: 99%
“…Phalloidin is known to primarily label the periodic actin lattice in dendritic spines in acute hippocampal sections (28). CaMKIIα-Cre is expressed highly in the hippocampus (23,29) as such, we consistently saw a decrease in SNAP-23 signals in the apical dendritic spines of CA1 neurons in the SNAP-23 cKO slices (Figure 1A and 1B). This decrease was also observed in the distal dendrites of the CA1 neurons (supplemental Figure 1).…”
Section: Generation Of Pyramidal Neuron-specific Snap-23 Cko Micementioning
confidence: 65%
“…This suggests that the LTP deficits are spatial learning and memory specific as demonstrated by poor Morris water maze performances, while deficits to the basal neurotransmission may affect other behaviors such as the hippocampus-dependent nestlet shredding task. The observed SNAP-23 cKO phenotypes are also different from that of syntaxin-3 cKO, as syntaxin-3 cKO led to no changes in LTP or basal neurotransmission as well as no changes in learning and memory (29). This suggests that the regulation of glutamate receptor trafficking in postsynaptic membranes are highly heterogenous, and requirements of specific SNARE proteins may depend on the neuronal activity state.…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot exclude the possibility that STX3 may be expressed in a small, specific subset of human brain cells, where it may impact human development or cognition. Early studies in mice suggested that STX3 may be involved in some types of learning and memory (Jurado et al 2013), but a subsequent study of the same brain region failed to reveal an effect of STX3 inactivation on basal synaptic function or on a specific type of synaptic plasticity or learning and memory tasks (Shi et al 2020). How might loss of STX3 function lead to photoreceptor degeneration?…”
Section: Discussionmentioning
confidence: 99%